Forensic genetic study of 29 Y-STRs in Korean population. (November 2016) - Jung, Ju Yeon; Park, Ji-Hye; Oh, Yu-Li; Kwon, Han-Sol; Park, Hyun-Chul; Park, Kyung-Hwa; Kim, Eun Hye; Lee, Dong-Sub; Lim, Si-Keun
Graphical abstract: Highlights: PPY23 and YPlus showed similar sensitivity, but PPY23 showed higher tolerance to humic acid than YPlus. The detection rate of unique minor alleles called from male/male mixtures was higher for PPY23 than for YPlus. Comparing the newly added loci, the mean values of gene diversity for PPY23 and YPlus were 0.6715 and 0.8158, respectively. The discrimination capacity in the 306 unrelated South Korean males for PPY23 was 0.9837, and that for YPlus was 0.9935. Abstract: In this study, we compared two recently released commercial Y-chromosomal short tandem repeat (Y-STR) kits: the PowerPlex Y23 System (PPY23) and Yfiler® Plus PCR amplification kit (YPlus). We performed validation studies, including sensitivity, tolerance to PCR inhibitors, and mixture analysis, and a population genetics study using 306 unrelated South Korean males. PPY23 and YPlus showed similar sensitivity, but PPY23 showed higher tolerance to humic acid than YPlus. Furthermore, the detection rate of unique minor alleles called from male/male mixtures was higher for PPY23 than for YPlus. Comparing the newly added loci, the mean values of gene diversity for PPY23 and YPlus were 0.6715 and 0.8158, respectively. The discrimination capacity in the 306 unrelated South Korean males for PPY23 was 0.9837, and that for YPlus was 0.9935. These results will inform the selection of suitable Y-STR kits based on the purpose of forensic DNA analysis.